The role of innate and lymphoid IL-22-producing cells in the immunopathology of primary Sjögren's syndrome. (April 2014) - Ciccia, Francesco; Guggino, Giuliana; Giardina, AnnaRita; Ferrante, Angelo; Carrubbi, Francesco; Giacomelli, Roberto; Triolo, Giovanni
Abstract : In primary Sjögren's syndrome (pSS) a complex of interconnections between epithelial barrier, innate and adaptive immunity occurs. IL-22 is a pleiotropic cytokine that in pSS may be placed at the intersection of the adaptive and innate branches of immunity. Some evidence suggests that, in pSS, IL-22 may play a prominent pro-inflammatory role driving the early phase of tissue and systemic inflammation and participating in the self-perpetuation of disease. Despite contradictory data in literature about the role of NK cells in pSS, recent data also suggest an important contribution of this subset of cells of the innate immune system in the development and perpetuation of inflammation. Here, we discuss the role of IL-22 in the pathogenesis of pSS and in epithelial barrier function.